A marxist reading of fitzgerald’s novel: The Great Gatsby and The Beautiful and Damned - Mostafa, Tasmia (BRAC University, 2016)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.